Development Learning Materials for the Responding Skills in Speaking the Basic Japanese Language –Beginning Step - Imelda Imelda; Aceng Rahmat; Nuruddin Nuruddin (Universitas Negeri Makassar, 2021)
This research aims at analyzing the students’ and lecturers’ needs and characteristics and creating the learning materials containing aizuchi skills to effectively speak the basic Japanese language greatly required by the first semester students at the Japanese literature Study. This research and development study employed Kemp Model and was conducted on the Speaking Basic Japanese Language 2 class. The research was conducted by collecting questionnaires from 24 students and analyzing the students’ and lecturers’ characteristics and needs in speaking the basic Japanese language using the Guttman scale. To create more appropriate leaning materials, a reliability test was conducted using the Likert scale, while an effectiveness test was also conducted on the in-pair speaking videos made in both small and big groups, each with the duration of three minutes to be analyzed later using the quantitative data. The result of research on the learning materials for the corresponding skills was organized based on the students’ and lecturers’ characteristics and needs analysis and produces the students’ and lecturers’ needs and students’ characteristics which are one of the elements in making development model of learning materials of responding skill in Speaking Basic greatly required by the students to speak communicatively and naturally.